Six-wavelength-switchable narrow-linewidth thulium-doped fiber laser with polarization-maintaining sampled fiber Bragg grating. (April 2021) - Zhang, Luna; Yan, Fengping; Feng, Ting; Han, Wenguo; Guan, Biao; Qin, Qi; Guo, Ying; Wang, Wei; Bai, Zhuoya; Zhou, Hong; Suo, Yuping
Highlights: A wavelength-switchable narrow-linewidth TDFL with a SFBG has been proposed. The laser got 6 single-wavelength and 9 dual-wavelength operations. The power/wavelength fluctuations of single-wavelength laser were 0.71 dB/0.02 nm. The linewidths of single-wavelength laser were among 0.60–1.08 kHz. The power/wavelength fluctuations of dual-wavelength laser were 0.95 dB/0.03 nm. Abstract: A compound-cavity-based six-wavelength-switchable single-longitudinal-mode (SLM) thulium-doped fiber laser (TDFL) with a homemade polarization-maintaining sampled fiber Bragg grating (PM-SFBG) is proposed and demonstrated. The PM-SFBG in the 2 μm band is studied theoretically and experimentally, and is utilized as a polarization-dependent multi-channel reflecting filter in a multi-wavelength-switchable fiber laser, both for the first time. The SLM lasing in each channel is guaranteed by using a tri-ring sub-cavity. 6 single-wavelength operations are easily obtained and switched each other, and the maximum power and wavelength fluctuations are as low as 0.71 dB and 0.02 nm, respectively. The frequency noise of each lasing wavelength is measured through an unbalanced Michelson interferometry system, and the linewidths for all six lasing wavelengths are among 0.60–1.08 kHz, calculated by the β -separation line method on the basis of the measured frequency noise spectra. Benefiting from the enhanced polarization hole burning effect formed in the gain fiber, 9 switchable dual-wavelength operations with different wavelength intervals and orthogonal polarizations at two lasing wavelengths are obtained with the maximum power and wavelength fluctuations of only 0.95 dB and 0.03 nm, respectively. We believe the proposed TDFL will find great applications as an ideal light source in free space optical communication and optical sensing.